Avaliação da aptidão motora e qualidade de vida de indivíduos da terceira idade praticantes da dança sênior - Klebis, Lucas Oliveira [UNESP]; Faria, Claudia Regina Sgobbi de [UNESP]; Mantovani, Alessandra Madia [UNESP]; Bofi, Tânia Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
INTRODUCTION: The expectation of longevity has increased due to technological advances in health. However, this fact is in competition with an active aging and a good quality of life of older people. The senescence process generates a progressive loss of independence of the elderly, also reducing their motor skills. Besides, the growing awareness of these physical disabilities generates insecurity and depression symptoms in this population. In this context, physical exercise, such as dance, is an important protection factor, preventing the appearance of chronic diseases caused by physical inactivity. Senior dance, made of choreography adapted to the needs of this population, provides not only the maintenance or improvement of physical fitness and motor skills, but also positive social experiences that help elderly people to restore self-esteem. OBJECTIVE: This study aims to identify a motor standard in individuals that practice Senior Dance as well as the quality of life of this population. METHODS:Using the Motor Scale for the Elderly (EMTI) and the Related Quality of Life to the Independent Senior Health Questionnaire (QUASI), being applied only once in 20 women, who were divided into two groups: Beginner (10) and Advanced (10), in accordance with the practice time of Senior Dance each. RESULTS AND DISCUSSION: It was observed improvement in all aspects evaluated in the instruments used but with difference statistically significant only in "body schema / speed" of the Motor Scale for the Elderly. When the values obtained were classified into motor ability levels, according to the manual of this, there was also a noticeable improvement in "fine motor" and "global motor" items. The item "General Motor Ability", which is the average of all items, was classified as "medium normal" in both groups, with a considerable improvement in the group practicing the dance for a year, although there was no signific ant difference . As for life's quality, there was no significant difference between the groups, although a slight improvement in the group practicing the activity a year ago. CONCLUSION: Even there was no significant difference between groups, an interesting improvement was seen in a year of activity, leading to the conclusion that the Senior Dance is a valid physical activity for the maintenance or improvement in motor ability and life's quality of individuals in old age. Although, studies with a larger number of participants and a longer practice time are needed.

INTRODUÇÃO: A expectativa de longevidade aumentou devido a avanços tecnológicos no âmbito da saúde, estando este fato em concorrência com um envelhecimento ativo e a melhor qualidade de vida desses indivíduos idosos. O processo de senescência gera uma perda progressiva da independência do idoso, além de diminuir suas capacidades motoras. Além disso, a percepção crescente dessas incapacidades físicas gera insegurança e quadros de depressão nessa população. Nesse contexto, o exercício físico, como a dança, é um importante fator de proteção, evitando o surgimento de doenças crônico-degenerativas causadas pelo sedentarismo. A dança sênior, composta por coreografias adaptadas às necessidades do idoso, proporciona não só a manutenção ou melhora do condicionamento físico e habilidades motoras desse indivíduo, mas também possibilita experiências sociais positivas que ajudam a restaurar a autoestima. OBJETIVO: Identificar um padrão motor em indivíduos praticantes de Dança Sênior, bem como a qualidade de vida dessa população. MÉTODOS: Utilizando a Escala Motora para a Terceira Idade (EMTI) e o Questionário de Qualidade de Vida Relacionada à Saúde de Idosos Independentes (QUASI), sendo aplicadas uma única vez, foram avaliadas 20 mulheres, divididas em dois grupos: Iniciante(10) e Avançado(10), de acordo com o tempo de prática da Dança Sênior de cada uma. RESULTADOS: Foi observado melhora em todos os aspectos avaliados nos instrumentos utilizados porém com diferença estatisticamente significante apenas no item “esquema corporal/rapidez” da Escala Motora da Terceira Idade. Quando os valores obtidos neste instrumento foram classificados em níveis de aptidão motora, segundo o manual deste, houve também uma notável melhora nos itens “motricidade fina” e “motricidade global”. O item “Aptidão Motora Geral”, que é a média entre todos os itens avaliados, foi classificada como “Normal médio” em ambos os grupos, tendo uma melhora considerável no grupo que pratica a dança há um ano, apesar de não haver diferença significativa. Quanto a qualidade de vida, não houve diferença significativa entre os grupos, apesar de discreta melhora no grupo que pratica a atividade há um ano. CONCLUSÃO: Apesar de não haver diferença significativa entre os grupos, uma melhora interessante foi observada em um ano de atividade, levando a concluir que a dança sênior é uma atividade válida para a manutenção ou melhora das habilidades motoras e da qualidade de vida em indivíduos na terceira idade. Ainda assim, estudos com um número maior de participantes e com um maior tempo de prática se fazem necessários.
Keywords: Sênior dance; Motor ability; Life's quality; Dança sênior; Aptidão motora; Qualidade de vida